Detection of flood-hazard-prone zones using GIS modeling and AHP method in urban areas: the case of Amman Governorate - Al-Sababhah, Noah (Bulletin of Geography. Physical Geography Series, 2023)
The aim of this study is to attempt a creative mapping of areas at risk of floods in Amman, using the Analytic Hierarchy Process (AHP) Method and GIS Modeling. The method (AHP) involves a weighting of a number of factors adopted by comparison. The main factors considered in this study were Elevation, Slope, Rainfall Intensity, Runoff, Land Use/Land Cover, Flow Accumulation, and SPI; these were reclassified and weighted to map the levels of flood hazards in the study area. Each factor/criteria was weighted and assigned a rank or score by using the Pairwise Comparison method to enable researchers to make a decision about the severity of the flood. The results show that about 28.2 % of the study area has a high to very high risk of flooding and that flooding can be very strong in the northwestern regions with high population density, while the risk becomes low in the eastern, southeastern, and western arid and semi-arid regions with low population density.